Implementation of the SIPRAJA Program Towards E-Government-Based Public Services: Implementasi Program SIPRAJA Menuju Pelayanan Publik Berbasis E-Government - Nisak, Khoirun; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2023)
This study explores the implementation of SIPRAJA, an e-government platform, in a rural Indonesian village. Using a qualitative approach and T.B. Smith's framework, we analyzed the interaction between policymakers, target groups, implementing organizations, and environmental factors influencing its adoption. Findings reveal positive community reception, highlighting SIPRAJA's potential to streamline public services. However, limited outreach and technical challenges raise concerns about inclusivity and sustainability. This research suggests targeted awareness campaigns and infrastructure improvements are crucial for bridging the rural-urban digital divide and maximizing the impact of e-government initiatives. Highlight : Positive community reception: SIPRAJA shows potential to improve public services in rural areas through streamlined access. Limited outreach and technical challenges: Concerns remain regarding inclusivity and sustainability due to lack of awareness and infrastructure. Bridging the digital divide: Targeted campaigns and infrastructure improvements are crucial for successful e-government initiatives in rural areas. Keywords: e-government, rural Indonesia, SIPRAJA platform, digital divide, inclusivity